Hospital Readmissions: Physician Awareness and Communication Practices - Roy, Christopher L. (Springer-Verlag, 2008)
BACKGROUND: Patients requiring early hospital readmission may be readmitted to different physicians, potentially without the knowledge of the prior caregivers. This lost opportunity to share information about readmitted patients may be detrimental to quality of care and resident education. OBJECTIVE: To measure physician awareness of and communication about readmissions. DESIGN: Cross-sectional study. SETTING: Two academic medical centers. PARTICIPANTS: A total of 432 patients discharged from the general medicine services and readmitted within 14 days. MEASUREMENTS: We identified patients discharged from the general medicine services and readmitted within 14 days, excluding patients readmitted to the same physician(s) and planned readmissions. We surveyed discharging and readmitting physicians 48 h after the time of readmission. RESULTS: Discharging physician teams were aware of 48.5% (95% CI 41.5%-55.5%) of patient readmissions. Communication between teams occurred on 43.7% (95% CI 37.1%-50.3%). Higher medical complexity was associated with an increased likelihood of physician communication (adjusted OR 1.12, 95% CI 1.06–1.19). When communication occurred, readmitting physicians received information about the discharging team’s overall assessment (61.9%, 95% CI 51.9%-71.9%), psychosocial issues (52.6%, 95% CI 42.4%-62.8%), pending tests (34.0%, 95% CI 24.2%-43.8%), and discharge medications (30.9%, 95% CI 21.5%-40.3%). When communication did not occur, most physicians (60.8%, 95% CI 56.7%-64.9%) responded it would have been desirable to communicate. CONCLUSIONS: Physicians are frequently unaware of patient readmissions and often do not communicate when readmissions occur. This communication is often desired and frequently results in the exchange of important patient information. Further work is needed to design systems to address this potential discontinuity of care.